2018
DOI: 10.1126/scisignal.aao1818
|View full text |Cite
|
Sign up to set email alerts
|

Splenic leukocytes define the resolution of inflammation in heart failure

Abstract: Inflammation promotes healing in myocardial infarction but if unresolved, it leads to heart failure. To define the inflammatory and resolving responses, we quantified leukocyte trafficking and specialized proresolving mediators (SPMs) in the infarcted left ventricle and spleen after myocardial infarction, with the goal of distinguishing inflammation from its resolution. Our data suggest that the spleen not only served as a leukocyte reservoir but also was the site where SPMs were actively generated after coron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 104 publications
(94 citation statements)
references
References 35 publications
4
90
0
Order By: Relevance
“…Diet interaction within the gut defines proximal, distal, and systemic inflammation, which in turn defines interorgan communication. The spleen is a secondary lymphoid organ and serves as a reservoir for the immune cells, regulating host defense or cardiac healing responses specifically in the event of HF (35, 39). The spleen is composed of RP and WP, which are separated by an interface, the MZ.…”
Section: Discussionmentioning
confidence: 99%
“…Diet interaction within the gut defines proximal, distal, and systemic inflammation, which in turn defines interorgan communication. The spleen is a secondary lymphoid organ and serves as a reservoir for the immune cells, regulating host defense or cardiac healing responses specifically in the event of HF (35, 39). The spleen is composed of RP and WP, which are separated by an interface, the MZ.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that modulating the MI-coordinated miRs could provide hints towards the regulation of post-MI inflammatory responses [62]. Wang et al have reported a cardio-protective role for miR-146a.…”
Section: Summary: Non-coding Rnas and Immune Regulationmentioning
confidence: 99%
“…From a translational perspective, whether other metabolic disease pathologies alter macrophage function, secretome, and phenotype in aging, needs to be investigated (14,43). In a recent study, Halade et al (44) quantitated leukocyte populations in the splenic reservoir and infarcted LV and further determined the concentrations of specialized proresolving mediators that limit cardiac inflammation post-MI. This study clearly suggests that leukocytes mobilize from the spleen to the infarcted heart to produce resolvins, lipoxins, maresins, and protectins in the infarcted heart during the acute inflammatory response, suggesting that acute inflammatory response coincides with resolving response in cardiac healing.…”
Section: Role Of Macrophages In Myocardium Healingmentioning
confidence: 99%
“…What is first in cardiac healing and repair after ischemic injury? Is it inflammation, or is it a resolution of inflammation, or do both overlap in a time-dependent manner to set the stage for healing program of myocardium after MI (44)? In response to injury, infection, or stress, an acute inflammatory response primarily involves early tissue edema within seconds to minutes followed by infiltration of neutrophils within minutes to hours and later mononuclear cells, some of which transition at maturity to macrophages.…”
Section: Future Prospectivementioning
confidence: 99%
See 1 more Smart Citation